Phase angle is moderately associated with short-term maximal intensity efforts in soccer players - Nabuco, H. C. G.; Silva, A. M.; Sardinha, L. B.; Rodrigues, F. B.; Tomeleri, C. M.; Ravagnani, F. C. P.; Cyrino, E. S.; Ravagnani, C. F. C. (International Journal of Sports Medicine, 2019)
This study examined the relationship between PhA and short-term maximal intensity efforts in soccer players, and was conducted in 99 male soccer players, ages 19-36 years. Bioelectrical impedance was used to assess body fat, fat free mass (FFM) and PhA (phase angle). Running Anaerobic Sprint Test (RAST) was used to evaluate physical performance. Food consumption was assessed through the 24-hour dietary recall method. Pearson correlation and multiple regressions were used for statistical analysis. Phase angle exhibited a positive relationship with maximum power (ß=0.66; P<0.001), even after adjustment for the co-variables FFM and body fat (ß=0.52; P=0.02). Phase angle was inversely related with fatigue index (ß=-0.61; P=0.04), even after adjusting for FFM (ß=-0.70; P=0.020). Our results indicated that independently of FFM and body fat, PhA was inversely associated with fatigue index and positively related with maximum power, revealing the PhA appeared as a valid predictor of fatigue.